Elaboration of fibrous structured activated carbon from olive pomace via chemical activation and low-temperature pyrolysis - Imad Alouiz; Mouhssine Benhadj; Elmontassir Dahmane; Mohamed Sennoune; Mohamed-Yassine Amarouch; Driss Mazouzi (Heliyon)
The objective of this study is to examine the preparation of activated carbon with a fibrous structure obtained from olive pomace through a chemical activation process using phosphoric acid (H3PO4) as the activating agent under air at a lower temperature. According to the findings, the most effective conditions to achieve high-performance activated carbon were 22 vol% of H3PO4, a 2-h chemical activation impregnation residence time at 50 °C, and a 500 °C pyrolysis temperature for 1 h. Structural analysis revealed that activated carbons possess highly developed textural and structural properties, resulting in an iodine value of 923 mg/g and a specific surface of 1400 m2/g. In addition to its microporosity, the produced carbon exhibits a highly developed fibrous structure, providing excellent adsorption properties. To confirm these results, SEM, FT-IR, XRF, XRD, Raman, and TGA techniques were employed. The fibrous carbon produced will expand the use of renewable carbon materials for removing various types of contaminants, including organic and inorganic pollutants in water, and numerous other industrial applications.